Chrysopogon zizanioides VOLATILE COMPOUNDS AS POTENTIAL INHALED THERAPEUTICS FOR METASTATIC LUSC BIOMARKER - Muhammad Faisal; Ilham Hariaji; Andy Sulaiman Siregar (JURNAL BIOSENSE, 2026)
Lung squamous cell carcinoma (LUSC) remains a major subtype of non-small cell lung cancer with limited therapeutic options, particularly in metastatic stages. This study aimed to identify extracellular matrix (ECM)-associated biomarkers involved in LUSC progression and evaluate volatile compounds from Chrysopogon zizanioides as potential inhaled therapeutic candidates through an integrated computational approach. Gene expression and survival analysis were performed using UALCAN and TNMplot databases to identify prognostic ECM-related biomarkers. Volatile compounds of C. zizanioides were screened using drug-likeness and toxicity prediction analysis. Molecular docking was subsequently conducted against representative COL6A3 domains, including the N2 domain, Kunitz-associated domain, and microfibrillar structure. Pharmacokinetic (PK) properties relevant to inhalation-based therapy were also assessed. The results demonstrated that COL6A3 was significantly overexpressed in tumor and metastatic LUSC tissues and associated with poor overall survival trends, suggesting its involvement in tumor microenvironment remodeling and metastatic progression. Among 30 identified volatile compounds, zizanal and khusitone exhibited favorable drug-likeness and low predicted toxicity profiles. Whole-protein and specific-site molecular docking analyses revealed that both compounds showed stronger binding affinities toward the microfibrillar region of COL6A3 than pirfenidone, with khusitone demonstrating the strongest interaction (-7.12 kcal/mol). Interaction analysis identified ARG2811 as a key residue contributing to ligand stabilization. Furthermore, PK prediction suggested favorable pulmonary-oriented characteristics, including efficient membrane permeability, low CYP450 interaction risk, reduced blood-brain barrier penetration, and moderate plasma clearance. Collectively, these findings suggest that zizanal and khusitone may serve as promising lead compounds for inhaled therapeutics targeting COL6A3-associated metastatic LUSC.